Whole-Genome Sequencing and Bioinformatic Analysis of Environmental, Agricultural, and Human Campylobacter jejuni Isolates From East Tennessee - Kelley, Brittni R.; Ellis, J. Christopher; Large, Annabel; Schneider, Liesel G.; Jacobson, Daniel; Johnson, Jeremiah G. (Frontiers in Microbiology, 2020)
As a leading cause of bacterial-derived gastroenteritis worldwide, Campylobacter jejuni has a significant impact on human health in both the developed and developing worlds. Despite its prevalence as a human pathogen, the source of these infections remains poorly understood due to the mutation frequency of the organism and past limitations of whole genome analysis. Recent advances in both whole genome sequencing and computational methods have allowed for the high-resolution analysis of intraspecies diversity, leading multiple groups to postulate that these approaches may be used to identify the sources of Campylobacter jejuni infection. To address this hypothesis, our group conducted a regionally and temporally restricted sampling of agricultural and environmental Campylobacter sources and compared isolated C. jejuni genomes to those that caused human infections in the same region during the same time period. Through a network analysis comparing genomes from various sources, we found that human C. jejuni isolates clustered with those isolated from cattle and chickens, indicating these as potential sources of human infection in the region.